ChemInform Abstract: Rh(III)‐Catalyzed Decarboxylative ortho‐Heteroarylation of Aromatic Carboxylic Acids by Using the Carboxylic Acid as a Traceless Directing Group. Issue 33 (August 2015) - Qin, Xurong; Sun, Denan; You, Qiulin; Cheng, Yangyang; Lan, Jingbo; You, Jingsong
Abstract The highly regioselective title reaction with various heteroarenes (e.g., thiophenes, furans, indoles, indolizines, azoles, and xanthines) uses the carboxylic acid as a traceless directing group.